Iron and the endurance athlete - Hinton, P. S. (Applied Physiology, Nutrition, and Metabolism, 2014)
Iron is a trace mineral that is highly significant to endurance athletes. Iron is critical to optimal athletic performance because of its role in energy metabolism, oxygen transport, and acid-base balance. Endurance athletes are at increased risk for suboptimal iron status, with potential negative consequences on performance, because of the combination of increased iron needs and inadequate dietary intake. This review paper summarizes the role of iron in maximal and submaximal exercise and describes the effects of iron deficiency on exercise performance. Mechanisms that explain the increased risk of iron deficiency in endurance athletes, including exercise-associated inflammation and hepcidin release on iron sequestration, are described. Information on screening athletes for iron deficiency is presented, and suggestions to increase iron intake through diet modification or supplemental iron are provided.